Pregunta
\[ \text{Find } 2011^2 - 2010^2 \text{?} \]
Ask by Davison Nguyen. in South Africa
Feb 16,2025
Solución de inteligencia artificial de Upstudy
Respuesta verificada por el tutor
Responder
The answer is 4021.
Solución
We can simplify 2011² - 2010² by using the difference of squares formula, which states:
a² - b² = (a - b)(a + b).
Plug in a = 2011 and b = 2010:
2011² - 2010² = (2011 - 2010)(2011 + 2010)
= 1 × (4021)
= 4021.
So, the answer is 4021.
Respondido por UpStudy AI y revisado por un tutor profesional
Como
error msg
![](/pmw/light_bulb.png?etag=525fd69ac661e11754e2fc9f1b18a4ee)
![](/pmw/spiral_notepad.png?etag=abe3906b7558c543a7b30ba53a3b5a5b)
Mind Expander
To solve for \( 2011^2 - 2010^2 \), we can use the difference of squares formula, which states that \( a^2 - b^2 = (a - b)(a + b) \). Here, let \( a = 2011 \) and \( b = 2010 \). So we have: \[ 2011^2 - 2010^2 = (2011 - 2010)(2011 + 2010) \] Calculating each part: 1. \( 2011 - 2010 = 1 \) 2. \( 2011 + 2010 = 4021 \) Now, plugging these back into the formula gives: \[ 2011^2 - 2010^2 = 1 \times 4021 = 4021 \] Thus, the value of \( 2011^2 - 2010^2 \) is \( \boxed{4021} \).
![](/pmw/img-try-permium.webp)
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium